Potential Of Transmission Of The Dengue Virus Based On Entomological Index And Maya Index In Kalumata And North Mangga Dua villages,Ternate City - Tomia, Amalan; Tuhatea, Rosmila (Publisher Cv. Inara, 2022)
Dengue hemorrhagic fever (DHF) is the result of the interaction between the dengue virus, humans and environmental factors. Dengue fever can be spread through the bite of the Aedes aegypti mosquito. Knowledge related to larval habitat is very important to limit the spread of Dengue virus by reducing the population level of Ae. aegypti. This study aims to determine the potential for dengue virus transmission based on the Entomological Index and Maya Index. The study was conducted in 2 villages in Ternate City for 1 month. To calculate the entomological index value, it is done by observing the characteristics of the habitat, namely by observing the container that is the habitat of Ae. aegypti. The calculated parameters are Container Index (CI), Breteau Index (BI), House Index (HI), Density Figure (DF), and calculate the BRI and HRI values to determine the virtual index. Based on the results of the study, it is known that the entomological index value of Kalumata and North Mangga Dua villages is CI 20.71%, HI 84.0% and BI 361%, with the average DF being in the high category (DF = 7 and 9). The virtual nidex value is in the medium category, namely MI = 55%, with a large BRI value = 56% (high category) and HRI = 45.5% (medium category), meaning that Kalumata and North Mangga Dua villages have the potential for virus transmission to occur Dengue.